Tame Italian ryegrass (Lolium multiflorum L.) enhancement in the argentine flooding Pampa: assessing winter forage production under grazing conditions - Danelon, Jose Luis (2013)
Effective operation of grazing production systems needs control the production of forage at farm level. A nine year old stand of enhanced tame native ryegrass (Lolium multiflorum L.) (RGE) and an annual crop of Italian ryegrass (Lolium multiflorum L. cv Tama) (RGT) were monitored to test the hypothesis that: (i) herbage biomass in such pastures can be assessed by Ration Calculation methodology as accurately as by more exhaustive procedures, and (ii) enhancement increases amount and quality of forage winter supply. Enhancement includes fertilization with NH4 NO3 and (NH4 ) 2 HPO4, and weed control with Glyphosate (N- (phosphonomethyl glycine)). The Ration Calculation method estimates available herbage dry matter assuming that «one herbage ration» equal to one cow equivalent (CE), consisting of 10 kg DM day-1 with 77.57 MJ of ME. Herbage samples were taken from each paddock, representing harvestable biomass. Grazing harvest efficiency and herbage DM intake (HDMI) were estimated through difference between initial (IHA) and final (FHA) herbage available (kg DM ha-1), before and after grazing, corrected by losses due to grazing. Eight grazing cycles of RGE produced 16 041 kg DM/ha year-1, (2 001 ± 79.3 rations/ha year-1) while ration calculation estimates 9 775 kg DM/ha year-1. The RGT allowed seven grazing cycles, yielded 12 269 kg DM/ha year-1 or 1 144 ± 87.1 rations/ha year-1 compared to 8 688 kg DM/ha year-1 estimated by calculating ration. The ration calculation method did not accurately assess the enhanced cumulative herbage DM produced. Enhancement technology improved production and quality of tame ryegrass in winter time.